A nonlethal sampling method to obtain, generate and assemble whole blood transcriptomes from small, wild mammals. (4th August 2015) - Huang, Zixia; Gallot, Aurore; Lao, Nga T.; Puechmaille, Sébastien J.; Foley, Nicole M.; Jebb, David; Bekaert, Michaël; Teeling, Emma C.
Abstract: The acquisition of tissue samples from wild populations is a constant challenge in conservation biology, especially for endangered species and protected species where nonlethal sampling is the only option. Whole blood has been suggested as a nonlethal sample type that contains a high percentage of bodywide and genomewide transcripts and therefore can be used to assess the transcriptional status of an individual, and to infer a high percentage of the genome. However, only limited quantities of blood can be nonlethally sampled from small species and it is not known if enough genetic material is contained in only a few drops of blood, which represents the upper limit of sample collection for some small species. In this study, we developed a nonlethal sampling method, the laboratory protocols and a bioinformatic pipeline to sequence and assemble the whole blood transcriptome, using Illumina RNA‐Seq, from wild greater mouse‐eared bats ( Myotis myotis ). For optimal results, both ribosomal and globin RNAs must be removed before library construction. Treatment of DNase is recommended but not required enabling the use of smaller amounts of starting RNA. A large proportion of protein‐coding genes (61%) in the genome were expressed in the blood transcriptome, comparable to brain (65%), kidney (63%) and liver (58%) transcriptomes, and up to 99% of the mitogenome (excluding D‐loop) was recovered in the RNA‐Seq data. In conclusion, this nonlethal blood sampling method provides an opportunity for a genomewide transcriptomic study of small, endangered or critically protected species, without sacrificing any individuals.